A microRNA signature for a BMP2-induced osteoblast lineage commitment program - Li, Zhaoyong (National Academy of Sciences, 2008)
Bone morphogenetic proteins (BMPs) are potent morphogens that activate transcriptional programs for lineage determination. How BMP induction of a phenotype is coordinated with microRNAs (miRNAs) that inhibit biological pathways to control cell differentiation, remains unknown. Here, we show by profiling miRNAs during BMP2 induced osteogenesis of C2C12 mesenchymal cells, that 22 of 25 miRNAs which significantly changed in response to BMP2 are down-regulated. These miRNAs are each predicted to target components of multiple osteogenic pathways. We characterize two representative miRNAs and show that miR-133 directly targets Runx2, an early BMP response gene essential for bone formation, and miR-135 targets Smad5, a key transducer of the BMP2 osteogenic signal, controlled through their 3′UTR sequences. Both miRNAs functionally inhibit differentiation of osteoprogenitors by attenuating Runx2 and Smad5 pathways that synergistically contribute to bone formation. Although miR-133 is known to promote MEF-2-dependent myogenesis, we have identified a second complementary function to inhibit Runx2-mediated osteogenesis. Our key finding is that BMP2 controls bone cell determination by inducing miRNAs that target muscle genes but mainly by down-regulating multiple miRNAs that constitute an osteogenic program, thereby releasing from inhibition pathway components required for cell lineage commitment. Thus, our studies establish a mechanism for BMP morphogens to selectively induce a tissue-specific phenotype and suppress alternative lineages.